1997
DOI: 10.1302/0301-620x.79b2.0790183
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Transpedicular Lumbosacral Fixation for Non-Traumatic Disorders

Abstract: W e analysed the complications encountered in 102 consecutive patients who had posterolateral lumbosacral fusion performed with transpedicular screw and rod fixation for non-traumatic disorders after a minimum of two years. Of these, 40 had spondylolysis and spondylolisthesis, 42 a degenerative disorder, 14 instability after previous laminectomy and decompression, and six pain after nonunion of previous attempts at spinal fusion without internal fixation. There were 75 multilevel and 27 single-level fusions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 25 publications
6
74
0
4
Order By: Relevance
“…Even if radiologically successful decompression and fusion is achieved, a neurological complication is extremely disturbing and negatively influencing the otherwise favourable reduction of radicular symptoms or spondylotic pain. Such a complication can occur as a result of nerve root compression, distraction or misplacement of pedicle screws [8].…”
Section: Introductionmentioning
confidence: 99%
“…Even if radiologically successful decompression and fusion is achieved, a neurological complication is extremely disturbing and negatively influencing the otherwise favourable reduction of radicular symptoms or spondylotic pain. Such a complication can occur as a result of nerve root compression, distraction or misplacement of pedicle screws [8].…”
Section: Introductionmentioning
confidence: 99%
“…Loosening of screws is a frequent problem in spinal instrumentation with pedicle screws [10,11]. It is often only noted as a radiolucency surrounding the pedicular screws, but in many cases loosening of the screws causes an unstable situation and loss of correction.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the instrumentation depends on the purchase of the pedicle screws in the pedicle and the vertebral body. Despite the fact that satisfactory clinical outcomes have been achieved with pedicle screw instrumentation, loosening of the screws, especially in the osteoporotic spine, still constitutes a significant problem [23,26] because it can lead to loss of correction or nonunion. To improve the stability of pedicle screw instrumentation, we have designed EPS and demonstrated that the instant fixation strength of the EPS was significantly higher than non-EPS.…”
Section: Discussionmentioning
confidence: 99%